2013
DOI: 10.1007/s11434-013-5751-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of chemical vapor generation in ICP-MS: A review

Abstract: Chemical vapor generation (CVG) is an important sample introduction technique, and is widely used for atomic spectrometry for its enhanced sensitivity and selectivity. In the past 30 years, inductively coupled plasma mass spectrometry (ICP-MS) has become a widely used and the most sensitive instrument for (ultra-)trace element determination and elemental speciation. A review of applications of this state-of-the-art coupling of CVG and ICP-MS is presented. Discussion is focused on its applications for both elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…Furthermore, it has been reported that use of reaction/collision cells may further enhance this sensitivity gap between As(III) and As(V) [9]. Chemical hydride generation (HG) has been widely used with ICPMS to enhance detection power and accuracy for the determination of As [12,13], principally due to efficient matrix isolation and enhanced introduction/ionization efficiency. However, because of the species-dependent efficiencies of reduction of the different forms of arsenic by reaction with NaBH 4 /KBH 4 , pre-conversion all As species to a single form is required [14e17].…”
Section: CLmentioning
confidence: 99%
“…Furthermore, it has been reported that use of reaction/collision cells may further enhance this sensitivity gap between As(III) and As(V) [9]. Chemical hydride generation (HG) has been widely used with ICPMS to enhance detection power and accuracy for the determination of As [12,13], principally due to efficient matrix isolation and enhanced introduction/ionization efficiency. However, because of the species-dependent efficiencies of reduction of the different forms of arsenic by reaction with NaBH 4 /KBH 4 , pre-conversion all As species to a single form is required [14e17].…”
Section: CLmentioning
confidence: 99%
“…Therefore, it is necessary to discuss the effects of the addition of selenium on trace element concentrations and their relocation in Danshen. Inductively coupled plasma-mass spectrometry (ICP-MS) has been widely used for the determination of trace and minor elements in a wide variety of traditional Chinese medicines due to its low detection limits, high selectivity, high accuracy, and the capability for multi-elemental analysis (Llorent-Martínez et al 2012;Abugassa et al 2008;Li, Zhong, and Lü 2012;Gao, Liu, and Yang 2013;Giannenas et al 2009). The determination of Hg and Se is often performed by hydride generation atomic fluorescence spectrometry (HG-AFS) due to its high sensitivity, few interferences, and broad linearity (Cai 2000;Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This study concluded that the use of the reflux systems is very rare in the determination of elements, such as Hg. Gao et al [ 137 ] reviewed the application of chemical vapor generation method for the determination of metal ions, such as mercury and cadmium with ICP-MS. Sańchez et al [ 138 ] reviewed the determination of trace elements including mercury present in petroleum products using ICP techniques. This study concluded that the electrothermal vaporization and laser ablation methods were promising for the analysis of petroleum for trace elements.…”
Section: Discussionmentioning
confidence: 99%